Case Report: Effective Treatment With Pyrotinib and Capecitabine in a Heavily Pretreated Locally Advanced Breast Cancer Harboring Both HER2 Overexpression and Mutant - Gao, Zhichao; Xu, Junnan; Wang, Yan; Wu, Jie; Sun, Tao (Frontiers in Oncology, 2021)
Locally advanced breast cancer (LABC) has poor prognosis, especially for those who are HER2 overexpression. Trastuzumab-based regimen has been the paradigm in guidelines as first-line therapy, whereas many patients got progressive disease after several cycles of treatment. Point mutations of ERBB2 gene occur in both HER2 positive and negative patients, with a 2% ratio in HER2 negative entity and 1.48% in HER2 positive ones. But in trastuzumab-treated patients, the ratio substantially raised to 16.7%-17.7%. ERBB2 mutation is one of the reasons which lead to traditional anti-HER2 drug resistance, as L755S and V842I indicates resistance to trastuzumab while L755S and K753I indicates resistance to lapatinib, while these mutations indicate sensitive to pan-HER tyrosine-kinase inhibitors. A 48-year woman diagnosed HER2-positive LABC developed trastuzumab-resistance after 3 lines of trastuzumab cross-line treatment with partial response (PR) as the best response, received next-generation sequencing (NGS), and discovered L755S in ERBB2 gene. Then she received effective treatment with pyrotinib plus capecitabine, and suffered mastectomy after 6 cycles of combined treatment with PR. Subsequently, she took pyrotinib as adjuvant therapy and achieved a long-term clinical benefit. In conclusion, pyrotinib is a potential neoadjuvant agent for the patients who were heavily pre-treated and harboring both ERBB2 overexpression and ERBB2 mutant in local advanced breast cancer.